2012
DOI: 10.1371/journal.pone.0044267
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of IFN-Induced Transcription Underlies IFN Defects Generated by Activated Ras/MEK in Human Cancer Cells

Abstract: Certain oncolytic viruses exploit activated Ras signaling in order to replicate in cancer cells. Constitutive activation of the Ras/MEK pathway is known to suppress the effectiveness of the interferon (IFN) antiviral response, which may contribute to Ras-dependent viral oncolysis. Here, we identified 10 human cancer cell lines (out of 16) with increased sensitivity to the anti-viral effects of IFN-α after treatment with the MEK inhibitor U0126, suggesting that the Ras/MEK pathway underlies their reduced sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 68 publications
1
38
0
Order By: Relevance
“…This contrasts with results using transformed human colonic cell lines that respond to rotavirus infection and poly(I:C) with type I IFN-β at the transcript and protein levels, and type I IFN regulates ISG induction in these cells (16,42,72). Transformed cells often have significant deficits in their response to pathogens, including in IFN signaling pathways (73,74). It seems likely that this critical difference in IFN responses to rotavirus and poly(I:C) between immortalized cell lines and nontransformed HIE cultures is partially attributed to their transformation status.…”
Section: Discussionmentioning
confidence: 72%
“…This contrasts with results using transformed human colonic cell lines that respond to rotavirus infection and poly(I:C) with type I IFN-β at the transcript and protein levels, and type I IFN regulates ISG induction in these cells (16,42,72). Transformed cells often have significant deficits in their response to pathogens, including in IFN signaling pathways (73,74). It seems likely that this critical difference in IFN responses to rotavirus and poly(I:C) between immortalized cell lines and nontransformed HIE cultures is partially attributed to their transformation status.…”
Section: Discussionmentioning
confidence: 72%
“…Lai et al have also reported that the decreased IFIT2 expression in human oral squamous cells can activate the PKC signaling pathway and promote the epithelial-mesenchymal transition (EMT) of the cancer cells [7]. Christian et al have also shown that the down-regulation of IFIT2 can be regulated by the activated Ras/MEK signaling pathway [19]. Lai et al have also found that the IFIT2 depletion can up-regulate the TNF-α secretion and further lead to angiogenesis and metastasis of OSCC cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…When murine embryonic fibroblasts (MEFs) were Ras-transformed in the presence of IRF1, it appeared to trigger p53-dependent growth-arrest and apoptosis; consequently, IRF1 −/− MEFs were more easily transformed [54,55]. Furthermore, it has been observed that Ras-transformed cells have down-regulated IRF1, which explains the reduced antiviral responsiveness of these cells [56,57]. Thus, IRF1 acts as a tumor suppressor during Ras-transformation and is selected against during tumorigenesis.…”
Section: Effect Of Immortalization On Antiviral Signalingmentioning
confidence: 99%